2012
DOI: 10.1097/dcr.0b013e31823f86a2
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Difficile of the Ileum Following Total Abdominal Colectomy, With or Without Proctectomy

Abstract: Black race is protective, and whites are 4 times more likely to acquire C difficile of the ileum after undergoing a total abdominal colectomy with or without proctectomy. The data also demonstrated that an increased age by a decade and emergency surgery are risk factors for C difficile enteritis, whereas the described risk factors of C difficile of the colon and type of colon surgery do not appear to influence the risk of C difficile of the ileum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Recognized CDI risk factors include advanced age, exposure to antibiotics, health care environment exposure, and possibly gastric acid suppression (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although previous studies suggested racial differences in CDI risks and mortality rates (14)(15)(16), the current literature does not identify race as a risk factor for CDI. This study utilized discharge data from the Nationwide Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality (www.hcup-us.ahrq.gov/nisoverview.jsp), to evaluate whether CDI rates vary with race, to explore confounders of the relationship between race and CDI rates, and to investigate whether racial disparities in CDI rates persist when confounders are minimized.…”
contrasting
confidence: 46%
“…Recognized CDI risk factors include advanced age, exposure to antibiotics, health care environment exposure, and possibly gastric acid suppression (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although previous studies suggested racial differences in CDI risks and mortality rates (14)(15)(16), the current literature does not identify race as a risk factor for CDI. This study utilized discharge data from the Nationwide Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality (www.hcup-us.ahrq.gov/nisoverview.jsp), to evaluate whether CDI rates vary with race, to explore confounders of the relationship between race and CDI rates, and to investigate whether racial disparities in CDI rates persist when confounders are minimized.…”
contrasting
confidence: 46%
“…Previous studies have suggested that black race may be protective of incident CDI 3840 whereas prior studies of recurrent CDI have not assessed race. 1214 The observed association between black race and CDI recurrence in the present study may be mediated by factors that influence the microbiome such as diet, biological differences such as a difference in mean serum albumin level, 41 or socioeconomic factors such as insurance status, access to medicines, or nursing home residency status.…”
Section: Discussionmentioning
confidence: 96%
“…Colectomy does not protect against CDI; rather, it may increase the risk of CDI in patients with ileostomies and ileo-anal reservoirs (J-pouch) 17 18. As the current case report indicates, patients with an ileorectal anastomosis following colectomy may acquire CDI.…”
Section: Discussionmentioning
confidence: 83%